«ELFINTEST» SOFTWARE FOR PROCESSING ENVIRONMENTAL MONITORING DATA BASED ON CLUSTER ANALYSIS - Курочкін, В. М. (Science-based technologies, 2015)
One of the popular topics for today about information technologies and mathematics practical use is the processing and analyzing digital data, especially photos and video material. A paper discusses the main issues relating to this topic, such as the problem of justifying the quality of the analysis and a large number of different types of factors that affect the result. Digital image processing, focusing attention on the specifics of the aerial data obtained by the UAV (unmanned aerial vehicle) is studied. The basic levels of image processing and methods of work with images are considered. The basic concepts of the implementation of the cluster analysis and the recognition are studied. The test software «ElfinTest», to create an environment for conducting experiments on real data and to determine the main and most informative features for textures that can be found on the data of aerial photography is constructed. The article presents some of the results of these studies in the form of digital images with more infographics and explanations based on real data.